Black and White Women’s Struggle during the Victorian Era Portrayed in The Various Flavors of Coffee Novel by Anthony Capella - Aisy, Rihhadatul; Setyowati, Ririn; Sartika Dewi Max, Jonathan Irene (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is expected to give readers the knowledge of understanding and appreciating literary works, especially those written about women. The methodology of this research is a descriptive qualitative method with a novel entitled The Various Flavors of Coffee (2008) written by Anthony Capella as the object. It analyzes the paragraphs, narrations, quotations and sentences from the novel that shows the theory of women struggle from the main female characters in order to be able to answer the research question. The results of this research shows how women struggled in five sectors in life, those are the working field, financial dependence, political rights, education, sexual exploitation and marriage.